What factors affect expatriate adjustment?: Study of differences between self-initiated and assigned expatriates in Poland - Grelecka, Joanna Dagmara (2017)
Finding and relocating workforce globally has been a huge part of Human Resources procedures in the 21st century. Expatriation possesses many advantages for both individual and hiring company however, many disadvantages are caused by interrupted expatriates‘ careers. One of the causes of expatriates‘ failure is difficulty of adjustment, in particular psychological, work environment, social and general living adjustment dimensions. A purpose of this comparative study was to look at the differences between self-initiated and assigned expatriation, antecedents and factors that may affect adjustment both positively and negatively. A total sample of 165 expatriates currently living and working in Poland was surveyed for this study. From the number of respondents 61 were assigned and 98 self-initiated expatriates, coming from various countries, in various age groups and with different amount of experiences. Results showed that, although the mere factor of affiliation to self-initiated or assigned expatriate did not have any effect on adjustment, various other factors, such as cultural distance, language proficiency, acculturation strategy or social support had significant impacts on adjustment.